2016
DOI: 10.1002/chem.201601826
|View full text |Cite
|
Sign up to set email alerts
|

Windmill Co4{Co44‐O)} with 16 Divergent Branches Forming a Family of Metal–Organic Frameworks: Organic Metrics Control Topology, Gas Sorption, and Magnetism

Abstract: A series of highly connected metal-organic frameworks (MOFs), [Co8 (O)(OH)4 (H2 O)4 (ina)8 ](NO3 )2 ⋅2 C2 H5 OH⋅4 H2 O (1), [Co8 (O)(OH)4 (H2 O)4 (pba)8 ](NO3 )2 ⋅8 C2 H5 OH⋅28 H2 O (2), and [Co8 (O)(OH)4 (H2 O)4 (pbba)8 ](NO3 )2 ⋅guest (3), in which ina=isonicotinate, pba=4-pyridylbenzoate, and pbba=4-(pyridine-4-yl)phenylbenzoate, is reported. These MOFs contain a new secondary building unit (SBU), with a square Co4 (μ4 -O) central unit having the rare μ4 -O(2-) motif, which is decorated by the other four pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…All dc and ac data reveal that Co 5 ‐INA displays unusual magnetic phenomena that can be attributed to a spin‐canted antiferromagnet with spin‐glass‐like relaxation , …”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…All dc and ac data reveal that Co 5 ‐INA displays unusual magnetic phenomena that can be attributed to a spin‐canted antiferromagnet with spin‐glass‐like relaxation , …”
Section: Resultsmentioning
confidence: 96%
“…Paramagnetic 3d metal ions have been widely employed for this purpose due to their interesting magnetic properties. Their use has afforded MOFs displaying various interesting magnetic phenomena such as single‐molecule magnetism (SMM),, , single‐chain magnetism (SCM),, spin canting,, metamagnetic transitions, spin glass relaxation, etc. Most of the magnetic MOFs are based on Co 2+ mainly because of the presence of three unpaired electrons in the high‐spin octahedral Co 2+ ion and its significant single‐ion magnetic anisotropy , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, almost all of the reported octanuclear cobalt oxide clusters exist in the discrete molecules. Only two polymeric structures constructed from the octanuclear cobalt oxide clusters as the basic units have been documented. , …”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, as a branch of rigid ligands, 4-(pyridin-4yl)benzoic acid (pba) has been widely adopted to build MOFs (Mehlana et al, 2015). Because of the simultaneous existence of the hard-base carboxylate group and the soft-base N-atom donor of the pyridyl ring, many pba-based MOFs with different topologies, like dia (Mehlana et al, 2012;Zhou et al, 2012;Elsaidi et al, 2014;Zeng et al, 2013;Zhang et al, 2017;Wang et al, 2017), pcu (Das et al, 2011;Zhang et al, 2011;, rtl (Zhou et al, 2014), tsi (Chen et al, 2016), hxl (Fang et al, 2013), bcu (Zeng, Zhou et al, 2010;Zhou et al, 2015), fsc (Elsaidi et al, 2016), ncb (Zhang et al, 2009(Zhang et al, , 2012Zhao, Mao et al, 2016), bnn (Fang, Zhang et al, 2015), tfz-d (Liu, Luo et al, 2014), mdf (Wang, Fang et al, 2010), sql , pts and qtz (Mehlana et al, 2013), have been reported. Moreover, a few novel topological pba-based MOFs with the Schlä fli symbols (3 6 Á4 18 Á5 3 Á6) (Ding et al, 2017), (8 4 Á12 2 )(8) 2 (Wang et al, 2018), and (3 3 Á4 12 Á5 3 Á6 3 )(3 6 Á4 12 Á5 9 Á6) (Fang, Cheng et al, 2014) have been known.…”
Section: Introductionmentioning
confidence: 99%